(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The rapid-fire elaboration of software development methodologies has needed the relinquishment of robotization- driven practices to enhance software quality and delivery speed. Continuous Integration (CI) and Continuous Delivery (CD) are foundation practices in ultramodern DevOps channels, enabling brigades to integrate law constantly, descry issues beforehand, and emplace operations fleetly with minimum homemade intervention. This exploration paper investigates the perpetration and optimization of CI/ CD channels using Amazon Web Services (AWS), a leading pall computing platform that offers scalable and intertwined DevOps tools. The study presents a methodical approach to constructing a CI/ CD workflow using AWS native services similar as AWS Code Commit for source control, AWS Code Build for automated testing and compendium, AWS Code Deploy for operation deployment, and AWS Code Pipeline for unity. The proposed channel is tested using a sample pall-native web operation and crucial criteria similar as figure time, deployment frequency, and failure recovery time are estimated. The exploration highlights the benefits of integrating CI/ CD practices with pall structure, including bettered software trustability, reduced deployment crimes, and enhanced development dexterity. Likewise, the paper discusses security considerations, cost- effectiveness, and scalability aspects associated with using AWS- managed CI/ CD services. The findings give practical perceptivity for software masterminds, DevOps interpreters, and experimenters seeking to apply flexible and effective software delivery channels in pall surroundings.